PSYCHOLOGICAL - PEDAGOGICAL BACKGROUND ACTIVATING ACTIVITIES IN INDIVIDUALLY CENTERED LEARNING - D. M. Nazarova, (Galaxy International Interdisciplinary Research Journal, 2022)
The paper gives a description of the process of activating the activity of students, discusses the aspects of development. The article also defines the main methodological principles.